Geografia em harmonias: a música como ferramenta para o ensino - Afonso, Raique Zambon (Universidade Federal de São Carlos, 2023)
This work aimed to analyze the potential use of music as a didactic and pedagogical tool for teaching Geography in high school. Additionally, the analysis of song lyrics related to teaching Geography topics helped identify how music can be used to convey concepts in a more accessible and engaging manner. The research methodology was based on the bibliographic review of various scientific articles and books related to the use of music in education and how it can help promote student engagement and motivation, as well as connect curriculum content with their daily experiences. Regarding the empirical research, the study conducted an online questionnaire with teachers who had experimented with using music in Geography classes. The results showed that using music in the teaching of Geography can have a positive impact on student engagement, motivation, and comprehension of the content. It was possible to demonstrate that the use of music can help create a more dynamic and interactive learning environment, as well as stimulate critical thinking and creativity among students. However, the study also identified some challenges that need to be addressed for the effective use of music in Geography education. One of the main challenges is the lack of material resources and training for teachers, which can hinder the implementation of innovative teaching practices. Another challenge is the need for a multidisciplinary and interdisciplinary approach to Geography education, which requires collaboration between different areas of knowledge and the integration of different teaching methodologies.
Geography in harmonies: music as a teaching tool
Geografía en armonías: la música como herramienta para la enseñanza
Keywords: Ensino de geografia; Análise de discurso musical; Análise de discurso musical; Teaching geography; Musical discourse analysis; Music and teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM